Laimaphelenchus australis sp. nov. (Nematoda: Aphelenchina) from exotic pines, Pinus radiata and P. pinaster, in Australia - Zhao, Zeng Q.; Davies, Kerrie A.; Riley, Ian T.; Nobbs, Jackie M. (Zootaxa, 2006)
Laimaphelenchus australis sp. nov. is described from bark of the exotic pines, Pinus pinaster from Kuitpo, South Australia, and Pinus radiata from Dartmoor, Victoria. This is the second record of Laimaphelenchus from Australia, and the first from exotic Pinus spp. The new species is characterised by having a tail with a single offset terminus, bearing 3–4 pedunculate tubercles, ending with 4–6 finger-like protrusions. In addition, the anterior region of the new species, as seen with SEM, lacks a distinct labial disc.Key words: Aphelenchina, Australia, Laimaphelenchus australis sp. nov., Nematoda, Pinus pinaster, Pinus radiata